A comparative study on the growth of InAlN films on different substrates. (15th August 2016) - Afzal, Naveed; Devarajan, Mutharasu; Ibrahim, Kamarulazizi
Abstract: This work investigates the growth of InAlN films on Si (111), sapphire (001), GaAs (100) and glass substrates and compares the structural, morphological, electrical and optical properties of these films. One micron thick InAlN films were synthesized on these substrates at 300 °C by using reactive magnetron co-sputtering system. The structural analysis showed the formation of polycrystalline InAlN films on all the substrates having preferred orientation along (101) plane. The films grown on sapphire and silicon displayed better structural quality than the films grown on GaAs and glass. The morphological results revealed identical granular features on all the substrates with small variation in the grain size. The electrical resistivity of InAlN film on sapphire was the lowest one (8×10 −3 Ω-cm) whereas the highest carrier concentration (8×10 20 cm −3 ) was obtained for the film deposited on glass. The energy band gap of InAlN films was determined through UV–vis absorption and reflectance spectroscopy. The band gap value obtained on the glass was slightly higher as compared to its value on the other substrates. The changes in InAlN properties on different substrates were explained on the basis of lattice mismatch, crystallite size, residual strain and orientation of the substrates.